Vegetative growth of upland rice and some pineapple varieties in intercropping at dryland Gunung Kidul, Yogyakarta - MUJI RAHAYU; DJOKO PRAJITNO; ABDUL SYUKUR (Society for Indonesian Biodiversity, 2006)
The aims of this research were to study vegetative growth of upland rice and some pineapple varieties in intercropping at dryland. The research was conducted from October 2003 until March 2004 at Logandeng village, Playen, Gunung Kidul regency, Yogyakarta province. The design of the field experiment was 3x2 factorial + 3 additional treatments arranged in randomized complete block. The first factor was pineapple varieties i.e. queen blitar (NB), queen hijau bogor (NQ) and cayenne subang (NC), while second factor was intercropping degree i.e. pineapple monoculture (P0) and 50% proportion of intercropping system (P50). The additional treatments consist of upland rice monoculture (P100), intercropping with proportion queen blitar 25%: 75% upland rice (P75) and intercropping with proportion queen blitar 75%: 25% upland rice (P25). The results of this research showed the best of upland rice growth on upland rice monoculture and the highest of pineapple growth on cayenne subang varieties monoculture. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: pineapple varieties, upland rice, intercropping, growth.